KINETICS STUDIES ON THE TAUTOMERIC REACTION OF 4-AMINO-5-METHYL-2,4-DIHYDRO-3H-1,2,4- TRIAZOLE-3-THIONE IN THE GAS PHASE: DFT AND CBS-QB3 METHODS USING TRANSITION STATE THEORY - Kazeminejad, Zahra; Shiroudi, Abolfazl; Pourshamsian, Khalil; Hatamjafari, Farhad; Reza Oliaey, Ahmad (Journal of the Chilean Chemical Society, 2019)
The isomerization reactions of the 4-amino-5-methyl-2,4-dihydro-3H-1,2,4-triazole-3-thione have been studied theoretically using density functional theory (DFT) along with various exchange-correlation functionals (B3LYP and M06-2x) as well as the benchmark CBS-QB3 quantum chemical approach. The calculated energy profile has been supplemented with calculations of kinetic rate constants by means of transition state theory (TST). Based on the optimized isomers geometries using the CBS-QB3 method, a natural bond orbital analysis reveals that the electronic delocalization from non-bonding lone-pair orbitals [LP(e)S7] to the neighboring σ* N2-C3 antibonding orbital increase from isomer 1 to isomer 2. Also, the LP(e)S7→σ* N2-C3 delocalizations could fairly explain the increase of occupancies of LP(e) non-bonding orbitals in the ring of isomers 1 and 2 (2 > 1). The electronic delocalization from LP(e)S7 non-bonding to σ* N2-C3 antibonding orbitals increase the ground state structure stability, Therefore, the increase of LP(e)S7→σ*N2-C3 delocalizations could fairly explain the kinetics of the isomerization reactions 1 and 2 (k2 > k1). NBO results also suggest that the kinetics of these processes are controlled by LP→σ* resonance energies.